New Challenges in Creating Value for Customers - the Value Co-Creation Process from the Customer Perspective - Bartkowiak , Paweł (Studia Oeconomica Posnaniensia, 2014)
In the first part of the article the concept of value co-creation is presented. The second part of the article contains the results of empirical research conducted in the following markets in the Poznań area: clothes and shoes, durable goods, fitness services, and mobile services. The presentation of the results focuses on the following research issues: (1) customers' tendency to participate in value co-creation, (2) the usefulness of customers' communication channels in the preparation or modification of a company's offering in various markets, (3) the perceived risks (opportunities or threats) connected with the preparation or modification of a company's offering in various markets and (4) an evaluation of purchase determinants that influence the preparation or modification of a company's offering in various markets.